Isolated Handwritten Vietnamese Character Recognition with Feature Extraction and Classifier Combination - Cuong, Le Anh; Dat, Ngo Tien; Ha, Nguyen Viet (VNU Journal of Science: Mathematics - Physics, 2010)
Abstract